Depopulation trends of rural areas of the Russian Federation according to the Russian Census 2020 - Vadim A. Bezverbny; Andrey N. Maksimov (Наука. Культура. Общество, 2022)
Based on the published data of the Russian Census 2020, as well as previous population censuses, the article calculates the dynamics of the rural population in all federal districts and constituent entities of the Russian Federation. The rural population in Russia is rapidly declining both in absolute and relative terms. Analysis of the results of the population censuses of 1959 and 1989 showed that in a period the rural population decreased by 17.1 million people, while the urban population increased by 46.9 million. According to the 2002 and 2020 censuses, the rural population decreased by 1.6 million people, and the share of the rural population in the total population in the period under review decreased from 27 to 25%. From the data obtained, it became clear that the share of the rural population decreased in all federal districts (from -0.7% to -2.9%), with the exception of the Far Eastern Federal District, where the share of the rural population increased by 1.2%. Only in 14 subjects of the federation there is an increase in the rural population in 2010-2020, but here it is also associated with the effects of suburbanization and the development of urban agglomerations, with administrative-territorial changes or increased fertility in some national republics. At the same time, in most regions (38 of those under consideration) there is a spatial contraction of the rural population, of which in 11 subjects of the federation it is of an accelerated nature. The article also presents the author's recommendations for changing the vector of demographic development of rural areas in Russia.